Effects of heat and mass flux on MHD free convection flow through a porous medium with radiation and first order chemical reaction - Awasthi, Bhavtosh (Zielona Góra: Uniwersytet Zielonogórski)
The study of a magneto hydrodynamic (MHD) free convection flow of an incompressible viscous fluid flow past a vertical surface is analyzed by taking into account viscous dissipation under the influence of radiation effect and chemical reaction with constant heat and mass fluxes. The governing partial differential equations have been converted into a set of ordinary differential equations using non dimensional quantities. The perturbation technique has been applied to solve the system of partial differential equations.
Keywords: first order chemical reaction; porous medium; viscous dissipation; MHD; radiation; heat fluxes; mass fluxes